Analysis of Boundary between Donggala Regency-Central Sulawesi and Mamuju Utara Regency-West Sulawesi Using Cartometric Method - Firdaus, Zahratu; Yuwono, Yuwono; Budisusanto, Yanto (Institut Teknologi Sepuluh Nopember, 2019)
Since the implementation of a vast autonomous region, real and responsible under law No. 22 of year 1999 about the local governance that is then replaced Act No. 23 of the year 2014, the boundary between the areas of concern that It is very important. In the era of regional autonomy, lots of good developments in the area of the village, district/city or province which holds the expansion. In practice, many local governments have trouble setting the boundaries of the region. One of them, namely the area between the boundaries of Donggala Regency North Mamuju and. The conflict limit the area of Donggala and Mamuju Regency North appeared as a result of the existence of a policy based on the area boundary Setup Kepmendagri No. 52 Year 1991 especially after installation of the Monument/Peg Limits on the area of the border between Donggala Regency North Mamuju less involving local communities.The purpose of this research is to provide a new boundary line between the Donggala Regency NorthÂ Mamuju and. Determination of the limits of this area using the appropriate kartometrik method Permendagri No. 76 Year 2012 about the guideline Assertion Limit area. From the results of the analysis of the territorial boundaries of the second district, obtained a map of territorial boundaries which allows alternatives to be used as consideration of dispute resolution in Donggala Regency and North Mamuju Regency